Preparation and Antibacterial Activity of Silver Nanoparticles Coated by Poly(vinyl pyrrolidone) - He, Guowen; Luo, Qiufan; Zhu, Mengxiang; Li, Fenfang (Asian Journal of Chemistry, 2014)
A silver nanoparticle with good monodispersity was produced by a convenient method for the reduction of silver nitrate in the presence of poly(vinyl pyrrolidone) as the surface modification agent. Silver nanoparticle had little effect on the chemical structure of poly(vinyl pyrrolidone). Silver nanoparticle modified by poly(vinyl pyrrolidone) with a nanosize of 5-10 nm had a face-centered cubic (FCC) crystalline structure and silver nanoparticle could develop a spherical morphology. Pure poly(vinyl pyrrolidone) have little antibacterial effect on bacteria and silver nanoparticle had perfect antibacterial activity with a wide antimicrobial spectrum against Gram-positive bacteria of Staphyloccocus aureus and Gram-negative bacteria of Escherichia coli. The antibacterial activity could be enhanced as increase of the silver nanoparticles concentration no matter what on Staphyloccocus aureus or Escherichia coli. Antibacterial activity of silver nanoparticles on Staphylococcus aureus was better than on Escherichia coli.